Methodology of formation the management skills during the studying process of Chemistry among the students of the 7th form (Pedagogy of Higher and Secondary Education, 2014)
Korostil L. A. Methodology of formation the management skills during the studying process of Chemistry among the students of the 7th form.On the basis of comparison and synthesis of scientific concepts of «organizational skills», «educational and management skills», «administrative skills», «self-education» we make the conclusion about necessity of management skills among students of comprehensive educational institutions in the conditions of the modern society. Author proposes a methodology of gradual formation of the management skills during the studying process of Chemistry among the students of the 7th form
Keywords: organizational skills; management skills; self-education; stages of skills formation